Teachersâ Implementation of Lesson Study to Preschoolers - Yuniar, Ghitha Loka; Justicia, Risty (Sebelas Maret University, 2016)
The point of departure in this article is to describe pre-schoolersâ learning during the study and the teachersâ expectations of each child learning experience through lesson study. Lesson study is a tool for building and sharing practitioner knowledge which the teachers are part of the research; they do planning, teaching, observing, and discussion about the lesson applied in a classroom. In Indonesia, lesson study is started to be commonly implemented in elementary to university level. But nowadays, preschool level is also improving to make the lesson study for early childhood education proper to be applied. One of preschool in Bandung which has opened a class for lesson study is Gagasceria preschool Bandung. In this case, qualitative descriptive, as a design, to describe the phenomenon, was utilized to get information on how the activities in the classroom carried out. The data were obtained from observation, field notes, and photos, as the units of analysis to research and understand the way teachers create meaning in their aims in teaching. Analysis of observation data showed that lesson study implementation of pre-schoolers is conducted by implementing the sequence of activity that generally can be divided into one set of preparation, before, during, and after teaching. By conducting lesson study, not only the pre-schoolers who got fun and meaningful learning, the teachers also got many benefits to improve their skill in teaching. With the references to findings, it is recommended that lesson study to preschool level is implemented to provide teaching-learning improvement in preschool.